Pengaruh Financial Technology, Literasi Keuangan, Inklusi Keuangan, Aksesibilitas Kredit Terhadap Keberlangsungan UMKM - Wiwiek Kusumaning Asmoro; Mohamad Arief Setiawan; Novie Astuti Setianingsih; Eti Putranti (Politeknik Ganesha Medan, 2025)
Rapid technological developments have made changes in various sectors one of them is the financial sector. Financial technology, Financial Inclusion, Financial Literacy and Credit Accessibility as One form of development in the financial sector. This study aims to determine the influence of Financial Technology, Financial Literacy, Financial Inclusion and Credit Accessibility on the Sustainability of MSMEs in Kediri City. This research data is primary data collected through a questionnaire using a technique with a purposive sampling approach. The population of 517 MSME actors in the Culinary Sector with the calculation of the sample of the slovin formula of respondents from MSMEs in Kediri City was 84 samples. The data was obtained from a questionnaire distributed to MSME owners in the Culinary Sector registered at the Kediri City Cooperative and SME Trade Office. This study uses multiple linear regression analysis with the application of SPSS 23. The results of the study show that financial technology. Financial literacy, financial inclusion and credit accessibility have a positive and significant effect on the sustainability of MSMEs. Therefore, it can be concluded that the importance of financial technology for MSMEs in developing their business as well as financial literacy, financial inclusion and credit accessibility will have an impact on MSME capital and business sustainability.